Cinnoline derivatives as human neutrophil elastase inhibitors; Journal of Enzyme Inhibition and Medicinal Chemistry; Vol. 31, iss. 4 - Giovannoni M. P. Maria Paola; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Crocetti L. Letizia; Ciciani G. Giovanna; Cilibrizzi A. Agostino; Guerrini G. Gabriella; Khlebnikov A. I. Andrey Ivanovich; Quinn M. T. Mark; Vergelli C. Claudia (2016, 2016)
Title screen